Improved predicting algorithm of RNA pseudoknotted structure. (2nd May 2019) - Liu, Zhendong; Zhu, Daming; Dai, Qionghai
The prediction of RNA structure with pseudoknots is NP-hard problem. According to minimum free energy models and computational methods, we investigate the RNA pseudoknotted structures and their characteristics. The paper presents an efficient algorithm for predicting RNA structures with pseudoknots, and the algorithm runs in O ( n 3 ) time and O ( n 2 ) space. The experimental tests in Rfam10.1 and PseudoBase indicate that the algorithm is more effective and precise, and the algorithm can predict arbitrary pseudoknots. And through our research, we can draw that there exists an 1 + ε ( ε > 0) polynomial time approximation scheme in searching maximum number of stackings, and we give the proof of the approximation scheme in RNA pseudoknotted structures.